The color of sex whiteness, heterosexuality, and the fictions of white supremacy - Stokes, Mason Boyd 1967- (New Americanists, 2012)
Introduction: White fictions. -- "De White man in season." -- Sympathy and symmetry: the romance of slavery in Metta V. Victor's Maum Guinea and her plantation "children". -- Someone's in the garden with Eve: race, religion, and the American fall. -- Charles Chesnutt and the masturbating boy: onanism, whiteness, and The Marrow of tradition. -- White sex: Thomas Dixon Jr. and the erotics of White supremacy. -- Becoming visible: I'm White, therefore I'm anxious. -- Epilogue: The queer face of Whiteness